SolarFlex Vision+ - Razali, Danish Firdouse; Halib, Muhammad Arif; Budiman, Muhammad Danish Fitri; Mat Zaki, Muhammad Zahriel (2024)
This paper introduces an innovative eyewear design that integrates advanced features to enhance user experience, comfort, and utility. The eyewear combines innovative technologies including an integrated flashlight, adjustable focal length, auto-contrast layer, solar-powered functionality, lightweight construction, and high durability. Crafted from premium materials such as carbon fiber or titanium alloy, the frame ensures both comfort and durability for extended wear. The adjustable focal length mechanism allows users to customize their vision according to individual needs, while the auto-contrast layer optimizes visibility in various lighting conditions. The integrated flashlight provides convenient illumination in low-light environments, enhancing safety and usability. The eyewear's solar-powered capabilities offer sustainable energy usage, ideal for outdoor activities or travel. Overall, this next-generation eyewear represents a significant advancement in vision enhancement technology, catering to the diverse needs of modern users with its blend of innovation, functionality, and durability.